Narrandera Shire - Gammage, Bill, 1942-; Narrandera (N.S.W. : Shire). Council ([Narrandera, N.S.W.] : Bill Gammage for the Narrandera Shire Council, 1986)
Includes chapter on Wiradjuri; Narrungdera; creation mythology, Baiame; totems; traditional life; contact with Europeans.
Includes index
Includes bibliographic references and index.
Bibliography: p. 252-259.
Keywords: Environment - Climate and weather - Floods; Stories and motifs - Creation / Cosmology; Recreation; Politics and Government - Political parties - Australian Labor Party; Occupations - Pastoral industry workers; Religion - Totemism; Politics and Government - Local government; Wiradjuri people (D10) (NSW SI55-07); Animals - Pets; Settlement and contacts - Settlers; Stories and motifs - Baiame; Animals - Mammals - Sheep; Narrandera (N.S.W.) -- History; Narrandera Region (N.S.W.) -- History; Narrandera (SW NSW SI55-10); Wagga Wagga (SW NSW SI55-15); Murdering Island (SW NSW SI55-10); Sandy Creek (Laura Qld SE Cape York SD55-13); Poisoned Waterholes Creek (SW NSW SI55-10)